PENGARUH NILAI MORAL DALAM AL-QUR’AN TERHADAP AKHLAK SISWA SDIT DARUL HASANAH BALIKPAPAN - Faiza Mahfudz; Iskandar Yusuf (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to examine the effect of moral values in the Qur'an on the moral character of students at SDIT Darul Hasanah Balikpapan. The research employed a quantitative approach using a survey design. The sample consisted of 20 students, and the data were collected through a questionnaire that had been tested for validity and reliability. Data analysis was conducted using simple linear regression with the assistance of IBM SPSS Statistics version 25. The findings indicated that the research instrument was valid and reliable. The hypothesis testing revealed a t-value of 4.612 with a significance value of 0.000 (p < 0.05), indicating that moral values in the Qur'an have a positive and statistically significant effect on students' moral character. Furthermore, the coefficient of determination (R Square) was 0.542, suggesting that 54.2% of the variation in students' moral character could be explained by moral values in the Qur'an, while the remaining 45.8% was influenced by other factors outside the scope of this study. These findings demonstrate that the better students understand and implement the moral values contained in the Qur'an, the better their moral character becomes. Therefore, strengthening the habituation of reading, understanding, and practicing the moral teachings of the Qur'an is essential for fostering students with noble character.